Design-Based Fingerprint Time Attendance System Using IOT With MCU Node ESP8266 - Nesha Putri Pratama; Agung Triayudi; Deny Hidayatulloh (Jurnal Teknik Informatika C.I.T Medicom, 2019)
Advances in technology and the world of electronics at the moment have entered the era of modernization and development has entered a new era and has been completely automated. One of them is the attendance machine for employees. Attendance machine needed for the industry to improve the effectiveness of work. So it takes the attendance machine that can work automatically in order to simplify the system works. The purpose of this study is to design a tool that would be used for a fingerprint recognition system. The attendance system design through the process of identifying the fingerprint pattern. Fingerprints identified by C3 Fingerprint sensor will indicate that the employee is absent from work. The fingerprint pattern has previously been registered in advance and recorded is the name, Fingerprint ID, position and time of entry. Once the data has been inputted kedatabasemaka be directly recorded that the employee is coming Works. The results of testing this system has a fingerprint identification accuracy with an average of 86.67%, and the average time matching fingerprintsebesar.